Nimbum Fugo: Campanas y Tormentas en la Nueva España (Tzintzun, Revista de Estudios Históricos, 2020)
From the colonial period to the present day, the bellâ€™s ring has accompanied the historical evolution of our Country. Historically, its clamor has been present in almost every of the most relevant civil and religious events. However, during the colonial era it also reported unforeseen natural events, and its sound was interpreted as a protective resource against extreme geological and hidrometeorogical phenomenon. This work is a first approach to studying the use of bell ringing to protect and ward of storms, floods and hails in the New Spain.